2011
DOI: 10.1111/j.1365-2230.2011.04108.x
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in psoriasis? An analysis of guidelines and systematic reviews published in 2009-2010

Abstract: SummaryThis review summarizes key clinical findings from 5 guidelines and 21 systematic reviews on psoriasis published or indexed in the period November 2009 to October 2010. The highlights include the British Association of Dermatologists guidelines on the use of biological interventions in psoriasis, and guidelines on the efficacy and use of acitretin. Biological therapies were reviewed for use in specific patient groups (such as those with hepatitis C) and from a health-economics perspective. Another system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
6
1
1
Order By: Relevance
“…In agreement with previous studies, they found a significant association of psoriasis with cardiovascular risk factors (diabetes mellitus and obesity) without, however, confirming an association with others (dyslipidemia and blood hypertension). In contrast, we found no significant difference in general medical history (e.g., cardiac diseases, diabetes) between psoriatic and control groups, except for high blood pressure that was more prevalent in psoriatic patients [2831]. …”
Section: Psoriasis and Metabolic Comorbiditiescontrasting
confidence: 75%
“…In agreement with previous studies, they found a significant association of psoriasis with cardiovascular risk factors (diabetes mellitus and obesity) without, however, confirming an association with others (dyslipidemia and blood hypertension). In contrast, we found no significant difference in general medical history (e.g., cardiac diseases, diabetes) between psoriatic and control groups, except for high blood pressure that was more prevalent in psoriatic patients [2831]. …”
Section: Psoriasis and Metabolic Comorbiditiescontrasting
confidence: 75%
“…Adalimumab or etanercept are considered first-line biologicals, ustekinumab is reserved as a second-line biological for patients where TNF antagonist therapy has failed or is contraindicated, and infliximab is advised when more rapid disease control is required. 33 However, toxicity and poor longterm efficacy have been seen for these drugs, for which the search for alternative strategies is required for the treatment of psoriasis. Anti-CD6 therapy is emerging as a new clinical approach for the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a life-threatening disease, it has significant morbidity, impact on quality of life2 and healthcare costs 3. A number of treatment options are available though none of them is entirely satisfactory 4. Thiazolidinediones (glitazones) have been found to be a novel therapeutic option in psoriasis 5 6…”
Section: Introductionmentioning
confidence: 99%